Ramanujan’s Notebooks 1998
DOI: 10.1007/978-1-4612-1624-7_3
|View full text |Cite
|
Sign up to set email alerts
|

Ramanujan’s Theories of Elliptic Functions to Alternative Bases

Abstract: Abstract.In his famous paper on modular equations and approximations to n , Ramanujan offers several series representations for X/n, which he claims are derived from "corresponding theories" in which the classical base q is replaced by one of three other bases. The formulas for \fn were only recently proved by J. M. and P. B. Borwein in 1987, but these "corresponding theories" have never been heretofore developed. However, on six pages of his notebooks, Ramanujan gives approximately 50 results without proofs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
133
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(137 citation statements)
references
References 2 publications
(2 reference statements)
1
133
0
3
Order By: Relevance
“…23-39], Ramanujan records several elegant series for 1/π and asserts, "There are corresponding theories in which q is replaced by one or other of the functions" q r := q r (x) := exp −π csc(π/r) 2 [11], who gave these theories the appellation, the theories of signature r (r = 3, 4, 6). An account of this work may also be found in Berndt's book [9,Chap.…”
Section: Ramanujan's Alternative Theories Of Elliptic Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…23-39], Ramanujan records several elegant series for 1/π and asserts, "There are corresponding theories in which q is replaced by one or other of the functions" q r := q r (x) := exp −π csc(π/r) 2 [11], who gave these theories the appellation, the theories of signature r (r = 3, 4, 6). An account of this work may also be found in Berndt's book [9,Chap.…”
Section: Ramanujan's Alternative Theories Of Elliptic Functionsmentioning
confidence: 99%
“…This theorem was first proved in print by Berndt, Bhargava, and Garvan [11], [9, p. 99], with (2.11) being a necessary ingredient in their proof. The analogues of (2.7) in the theory of signature 3 are given by [9, p. 109, Lemma 5.1]…”
Section: Ramanujan's Alternative Theories Of Elliptic Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recall from [20] that for a, b ∈ N the series means that the summation does not include (m, n) = (0, 0).) Then Bloch introduced the regulator function R E (e 2πiu ) = Im(τ ) 2 π K 2,1 (τ ; u). It can be shown that Re(R E ) = D E , and that − Im(R E ) is the real-valued function given by…”
Section: Introductionmentioning
confidence: 99%